Topônimos do noroeste do Rio Grande do Sul: uma relação simbólica entre homem e lugar - Marcuz, Ligia Manara Miletto (2016)
Toponymy systematizes the names of places, describes the structure and formation of these names, being translated into a form of identification, orientation, and referral. On the assumption that names of places have an intimate association with the cultural values of the people, they reflect the historical relevance of facts and customs, besides directly dealing with discovery, occupation, and ownership of geographical space. In light of this, this study aims at studying the proper names of places, in the northwest region of Rio Grande do Sul, based on the route of Jesuit presence in this state the Seven Peoples of the Mission -, named classical phase, the period between 1682 and 1756, conducting identification, classification, and spatialization of these toponyms. The region chosen for this study is of great cultural richness and target of many researches. However, studies that approach the local toponymy are unknown. In order to implement this study, besides the geographical focus, a historical retrospective was conducted over the first attempts of the colonizers of the northwest of Rio Grande do Sul, a review of toponymy and its classification models, as well as a study about the place while geographic category of analysis. This research, of qualitative and quantitative approach, began with a biographical and documental exploratory study and made use of fieldwork to broaden the possibilities of data collection. The categorization of the toponyms found was based on the taxonomy presented by Dick (1990a), used for the Brazilian reality. The processes of formation, structuring, and motivation of toponyms were analyzed through lexicographic-toponymic files, that integrate the methodological base of the study of toponyms. The data analysis showed toponymy as one of the possibilities to understand the land formation, since the names of places are a kind of repository that contains he memory and history of the place, manifested by the temporal layers of space occupation. After around 400 years since the formation of the first Jesuit-Guaraní reduction in the state, these toponyms remain as live presence of a way of interaction and spatial occupation, by different cultures and their way of interacting among themselves and with nature, and they prove that the initial memory of the northwest of Rio Grande do Sul is closely connected to the presence of indigenous peoples and European missionaries in that space.